Management of the 2023 ASKOT PSSI KU-12 Semarang City Football School League (SSB) - Rilo Pratama; Harry Pramono; Mugiyo Hartono (Journal of Physical Education and Sports, 2023)
This research aims to 1) Analyze the human resource management process for organizing the School Football League (SSB); 2) Analyze the management process of school football league (SSB) information publication; 3) Analyze the management process of Facilities and Infrastructure for the School Football League (SSB); and 4) Analyzing the funding management process for the Askot PSSI KU-12 Semarang City Football School League (SSB) in 2023. This research is a qualitative descriptive study. The approach used is the management function Planning, Organizing, Actuating, Controlling (POAC) by combining 5M elements of management resources (Man, Money, Material, Method, Machine). Data collection techniques are interviews, observation and documentation as for the research subjects of the Semarang City PSSI Askot management , Referee and SSB league participant. Data analysis uses interactive and naturalistic interpretation. The research results show: 1) Human resources are minimal, resulting in duplicate tasks; 2) the delivery of information on the field is less updated, less detailed and tends to be inconsistent 3) carrying out inventory and infrastructure according to competition needs, especially the field uses a rental system with the government or village officials as managers 4) financial management shows a lack of funds resulting in the committee making changes to the budget allocation operations, not all of them have physical evidence or digital traces of transactions. Conclusion Suggestions 1) The management adds supporting staff, provides education on how to organize matches with full High Integrity. 2) the publication of information is formulated carefully and clearly regarding content, delivery time, updated news and complaint procedures 3). Responsible for lost equipment, periodizing equipment maintenance 4) increasing relationships to be able to raise more funds with mandatory proof of transactions.